2015
DOI: 10.4103/1673-5374.160112
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of bowel program in spinal cord injury patients with neurogenic bowel dysfunction

Abstract: In this study, we aimed to determine gastrointestinal problems associated with neurogenic bowel dysfunction in spinal cord injury patients and to assess the efficacy of bowel program on gastrointestinal problems and the severity of neurogenic bowel dysfunction. Fifty-five spinal cord injury patients were included in this study. A bowel program according to the characteristics of neurogenic bowel dysfunction was performed for each patient. Before and after bowel program, gastrointestinal problems (constipation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 17 publications
2
47
1
2
Order By: Relevance
“…R Yasmeen had reported that 43 of 50 adult patients with SCI in Pakistan gave a history of occasional or regular fecal incontinence (38). The prevalence of NBD in SCI patients was 80% in previous study, 97.3% of motor complete SCI patients had chronic NBD complaints in their study (10), which was similar with patients had a constipation in our study. The patients in our study had to spend much time on defecation in their long course of SCI to deal with NBD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…R Yasmeen had reported that 43 of 50 adult patients with SCI in Pakistan gave a history of occasional or regular fecal incontinence (38). The prevalence of NBD in SCI patients was 80% in previous study, 97.3% of motor complete SCI patients had chronic NBD complaints in their study (10), which was similar with patients had a constipation in our study. The patients in our study had to spend much time on defecation in their long course of SCI to deal with NBD.…”
Section: Discussionsupporting
confidence: 88%
“…Among them, neurogenic bowel dysfunction (NBD) is a major physical and psychological problem in patients with SCI, which can seriously affect the quality life of patients. The two main manifestations of NBD are constipation and fecal incontinence, with the prevalence of constipation in these patients reported to be 40–58%, and fecal incontinence from 2 to 61% (8,9,10,11). Because of these problems, patients with chronic SCI tend to spend more time in the toilet while evacuating their bowels, use suppositories, laxatives and supplemental dietary fiber more frequently to improve bowel evacuation and require manual removal of feces much more frequently when compared with their matched control population (12,13,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The injury of nerves that control rectal defecation reflex results in the disappearance of defecation reflex. Prolonged stay of stool in rectum and water absorption led to the occurrence of dry stool (Ozisler, Koklu, Ozel, & Unsal-Delialioglu, 2015). Due to the bowel dysfunction, patient diet is limited and they cannot participate in normal work and life.…”
Section: Discussionmentioning
confidence: 99%
“…6,8 The effect of a bowel program on different neurogenic bowel symptoms including abdominal pain supports the relation between abdominal pain and constipation. 13 However, it is possible that neuropathic pain contributes to abdominal pain in some of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 Abdominal pain is not associated with completeness or the level of SCI, 5,7 and the underlying mechanisms are likely to vary among SCI individuals and may be related to both visceral and neuropathic pain mechanisms. [6][7][8][9][10][11][12][13] Abdominal pain has a late onset after SCI, and although it is relatively uncommon in the first 5 years, 2,4-5 it has been reported in 22% at 10 years and in up to 34% of SCI individuals at 20 years after SCI. [5][6] However, little is known about the time course of abdominal pain once it has developed.…”
Section: Introductionmentioning
confidence: 99%